Introducing the Concept of Exercise Holidays for Human Spaceflight - What Can We Learn From the Recovery of Bed Rest Passive Control Groups - Ekman, Robert; Green, David A.; Scott, Jonathon P. R.; Huerta Lluch, Roger; Weber, Tobias; Herssens, Nolan (Frontiers in Physiology, 2022)
In an attempt to counteract microgravity-induced deconditioning during spaceflight, exercise has been performed in various forms on the International Space Station (ISS). Despite significant consumption of time and resources by daily exercise, including around one third of astronauts’ energy expenditure, deconditioning – to variable extents – are observed. However, in future Artemis/Lunar Gateway missions, greater constraints will mean that the current high volume and diversity of ISS in-flight exercise will be impractical. Thus, investigating both more effective and efficient multi-systems countermeasure approaches taking into account the novel mission profiles and the associated health and safety risks will be required, while also reducing resource requirements. One potential approach is to reduce mission exercise volume by the introduction of exercise-free periods, or “exercise holidays”. Thus, we hypothesise that by evaluating the ‘recovery’ of the no-intervention control group of head-down-tilt bed rest (HDTBR) campaigns of differing durations, we may be able to define the relationship between unloading duration and the dynamics of functional recovery – of interest to future spaceflight operations within and beyond Low Earth Orbit (LEO) – including preliminary evaluation of the concept of exercise holidays. Hence, the aim of this literature study is to collect and investigate the post-HDTBR recovery dynamics of current operationally relevant anthropometric outcomes and physiological systems (skeletal, muscular, and cardiovascular) of the passive control groups of HDTBR campaigns, mimicking a period of ‘exercise holidays’, thereby providing a preliminary evaluation of the concept of ‘exercise holidays’ for spaceflight, within and beyond LEO. The main findings were that, although a high degree of paucity and inconsistency of reported recovery data is present within the 18 included studies, data suggests that recovery of current operationally relevant outcomes following HDTBR without exercise – and even without targeted rehabilitation during the recovery period – could be timely and does not lead to persistent decrements differing from those experienced following spaceflight. Thus, evaluation of potential exercise holidays concepts within future HDTBR campaigns is warranted, filling current knowledge gaps prior to its potential implementation in human spaceflight exploration missions.